Salicylic Acid Induction of Flavonoid Biosynthesis Pathways in Wheat Varies by Treatment - Gondor, Orsolya K.; Janda, Tibor; Soós, Vilmos; Pál, Magda; Majláth, Imre; Adak, Malay K.; Balázs, Ervin; Szalai, Gabriella (Frontiers in Plant Science, 2016)
Salicylic acid is a promising compound for the reduction of stress sensitivity in plants. Although several biochemical and physiological changes have been described in plants treated with salicylic acid, the mode of action of the various treatments has not yet been clarified. The present work reports a detailed comparative study on the effects of different modes of salicylic acid application at the physiological, metabolomic, and transcriptomic levels. Seed soaking and hydroponic treatments were found to induce various changes in the protective mechanisms of wheat plants. The possible involvement of the flavonoid metabolism in salicylic acid-related stress signaling was also demonstrated. Different salicylic acid treatments were shown to induce different physiological and biochemical processes, with varying responses in the leaves and roots. Hydroponic treatment enhanced the level of oxidative stress, the expression of genes involved in the flavonoid metabolism and the amount of non-enzymatic antioxidant compounds, namely ortho-hydroxycinnamic acid and the flavonol quercetin in the leaves, while it decreased the ortho-hydroxycinnamic acid and flavonol contents and enhanced ascorbate peroxidase activity in the roots. In contrast, seed soaking only elevated the gene expression level of phenylalanine ammonia lyase in the roots and caused a slight increase in the amount of flavonols. These results draw attention to the fact that the effects of exogenous salicylic acid application cannot be generalized in different experimental systems and that the flavonoid metabolism may be an important part of the action mechanisms induced by salicylic acid.